Peningkatan Kompetensi Profesional Guru Dalam Menyusun Laporan Penelitian Tindakan Kelas Melalui Model Pembinaan CLCK (Contoh, Latihan, Control, Kerja Mandiri) Berbasis Mentoring MIN 10 Aceh Barat Daya Tahun Pelajaran 2018/2019 - Daswati, Daswati (Universitas Serambi Mekkah, 2020)
Based on observations of the MIN 10 Aceh Barat Daya teacher's competence in compiling school action research reports, it was found that the teacher's professional competence in compiling classroom action research was still low. The purpose of this study is to describe and obtain information about improving teacher professional competence in developing classroom action research reports through a mentoring model based on CLCK (Example, Exercise, Control, Independent Work) in MIN 10 Southwest Aceh. This research is a School Action Research (PTS). Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 6 MIN 10 Southwestern Aceh teachers. Research data were collected using observation sheets. Data were analyzed using percentages. Based on the results of research and discussion, it can be concluded that the mentoring model based on CLCK development can improve the ability of teachers in preparing classroom action research reports in MIN 10 Southwest Aceh. Analysis of the quality of PTK reports made by teachers shows that the teacher's professional competence in preparing class action research reports increases from cycle I to cycle II. The teacher's professional competence in preparing the class action research report in cycle I was 76.50 (Good) increased to 87.16 (Very Good) in cycle II with an increase of 10.66 points.